Pengembangan E-Modul Otomatisasi Tata Kelola Kepegawaian Berbasis Android Pada Materi Semester Gasal Kelas XI OTKP 2 di SMK PGRI 2 Sidoarjo - Dyah Retno Ismiarti; Choirul Nikmah (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Learning resources is one of the needs in the learning process. To ensure the learning process conducted effectively, learning resources must fulfill requirement of curriculum, such as by using technology to get facilities of access and flexibility in learning. This journal aims to develop learning resources, determine the appropriateness of learning resources, and determine student responses through the development of the Governance Staffing Automation Based on Android and Scientific e-module on Class XI OTKP 2 Odd Semester Material at SMK PGRI 2 Sidoarjo. To carry out these developments, a 4-D research model was used with data collection in the form of material expert validation, language expert validation, graphic expert validation and student responses. The results of the study stated that the e-modules developed in the category were very suitable to be used as learning resources in terms of validations result of material feasibility is 96,57%, language feasibility 95,71%, and feasibility of graphic 92,67%. If averaged, the result of product feasibility obtained a percentage of 94,98%. Then, the student response results obtained score of 94,58%.